Low Voltage CMOS Schmitt Trigger In 0.18μm Technology - Arith, Faiz; Idris, Muhammad Idzdihar; Zainudin, Muhammad Noorazlan Shah; Mohd Chachuli, Siti Amaniah (IOSRJEN, 2013)
This paper presents the effect of source voltage on performance of proposed Schmitt Trigger circuit. The proposed circuit was designed based on Conventional Schmitt Trigger by manipulating the arrangement of transistors and the width-length ratio. The simulation results have been carried out based on Mentor Graphics software in term of propagation delay. The circuit layout has been designed and checked by using design rule check (DRC) and layout versus schematic (LVS) method. From these results, the proposed full swing CMOS Schmitt Trigger was able to operate at low voltage (0.8V-1.5V)